Meta-Analysis: The Influence of Knowledge, Hormonal Contraceptive Use, and Sexually Transmitted Disease on Cancer Screening Uptake - Diani Fadmi Putri; Andri Setiawan; Nathanael Aditya Santoso; Bhisma Murti; Nindita Arum Veibiani (Masters Program in Public Health, 2025)
Background: Cervical cancer is still the most common problem among women. Prevention of cervical cancer can be done prospectively through human papillomavirus (HPV) vaccination and screening or early diagnosis. Screening is essential to reduce the incidence and death of cervical cancer. This study aims to analyze and estimate the influence of knowledge, the use of hormonal contraceptives, and the history of sexually transmitted diseases on cervical cancer screening. Subject and Method: This study is a meta analysis using the PRISMA flowchart and the PICO model. Population: women of childbearing age. Intervention: using hormonal contraceptives, having good cervical cancer knowledge, and having a history of sexually transmitted infections. Comparation: not using hormonal contraceptives, poor cervical cancer knowledge and no history of sexually transmitted infections. Outcome: cervical cancer screening. The process of searching for articles by searching through databases in Google scholar, Scopus, ProQuest, PubMed, Elsevier, and Science direct. The keywords used are